A influência da iluminação natural no ambiente escolar: o impacto do ofuscamento em crianças nas salas de aula de escolas municipais de João Pessoa - Costa, Tainá Gomes dos Santos (2022)
Glare is a visual disturbance caused when one part of a place has excess light compared to the other part, being a frequent nuisance in school environments. The non-uniformity in the distribution of illuminance and other factors, result in problems with glare that can cause from uncomfortable sensations to impairments in children's learning. As visual perception is subjective, there is a gap in studies involving lighting, especially with children. The general objective of this work is to evaluate the visual comfort of children in classrooms of three elementary schools in João Pessoa, according to their different positions in the desks, at different times. The research was developed from computer simulations of lighting in the Apolux IV program, with emphasis on school classrooms, and from comparative analyzes with in loco data collection, using generalized linear models according to the data collected. The rooms with the most significant illuminance values had the openings facing northwest and southeast, and the results confirm that the positions closer to the blackboard, the positions next to the window and those opposite the opening, cause greater contrast in the visual field. and a consequent greater possibility of a sensation of glare. It is concluded that the students' position in the classroom and the incidence of light on the board and desks cause visual contrasts due to the heterogeneity of illuminance. In order to obtain greater visual comfort, an environment with a more homogeneous illuminance is necessary, especially in the front area of the classrooms and next to the window, in order to reduce the discomfort caused by the contrasts of lighting.